2010
DOI: 10.1523/jneurosci.2313-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Reaching Activity in the Medial Posterior Parietal Cortex of Monkeys Is Modulated by Visual Feedback

Abstract: Reaching and grasping an object is an action that can be performed in light, as well as in darkness. Area V6A is a visuomotor area of the medial posterior parietal cortex involved in the control of reaching movements. It contains reaching neurons as well as neurons modulated by passive somatosensory and visual stimulations. In the present work we analyze the effect of visual feedback on reaching activity of V6A neurons. Three macaques were trained to execute reaching movements in two conditions: in darkness, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 45 publications
(65 reference statements)
8
48
0
Order By: Relevance
“…All of these data support the view that V6A uses visual information for the on-line control of goal-directed hand actions Bosco et al, 2010). Present findings are consistent with the hypothesis that visual mechanisms mediating the control of skilled actions directed to target objects are functionally and neurally distinct from those mediating the perception of objects (Goodale et al, 1994).…”
supporting
confidence: 89%
“…All of these data support the view that V6A uses visual information for the on-line control of goal-directed hand actions Bosco et al, 2010). Present findings are consistent with the hypothesis that visual mechanisms mediating the control of skilled actions directed to target objects are functionally and neurally distinct from those mediating the perception of objects (Goodale et al, 1994).…”
supporting
confidence: 89%
“…Recorded cells were assigned to V6Av or V6Ad on the basis of the cytoarchitectural pattern of recording sites (Luppino et al, 2005). The functional properties of many neurons have been described in our previous studies (Galletti et al, 1996(Galletti et al, , 1999aFattori et al, 2001Fattori et al, , 2005Fattori et al, , 2009Fattori et al, , 2010Breveglieri et al, 2002;Bosco et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…A detailed description of the methodologies used to study reaching activity is reported in recent works by Fattori and coworkers Bosco et al, 2010).…”
Section: Motor-related Activitymentioning
confidence: 99%
“…V6A is strongly connected with PPC areas that encode eye movements and fixations in depth, like the lateral intraparietal area (LIP) and area 7a (Gamberini et al, 2009;Passarelli et al, 2011). It also contains neurons modulated by arm-reaching movements in 3D space Marzocchi et al, 2008;Bosco et al, 2010), and by gaze position in a frontoparallel plane (Galletti et al, 1995;Nakamura et al, 1999).…”
Section: Introductionmentioning
confidence: 99%